2012
DOI: 10.1093/molbev/mss220
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the ARF Gene Family in Land Plants: Old Domains, New Tricks

Abstract: Auxin response factors (ARF) are key players in plant development. They mediate the cellular response to the plant hormone auxin by activating or repressing the expression of downstream developmental genes. The pivotal activation function of ARF proteins is enabled by their four-domain architecture, which includes both DNA-binding and protein dimerization motifs. To determine the evolutionary origin of this characteristic architecture, we built a comprehensive data set of 224 ARF-related protein sequences that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
219
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(249 citation statements)
references
References 61 publications
21
219
1
8
Order By: Relevance
“…As the ARF family traces its origins back to the first land plants, we investigated whether the maize and Arabidopsis ARF binding properties have diverged in the 140-150 million years since their last common ancestor (Finet et al, 2013). Testing a maize co-ortholog of ARF5 (ZmARF29; Galli et al, 2015) on maize gDNA (Zm-gDNA) by DAP-seq, we observed similar, but not identical, motif spacing preferences with two dominant spacing groups in maize compared to the eight more distributed groups in Arabidopsis ( Figure 6C).…”
Section: Cooperative Binding Of Arf Homodimers At Phased Motif Repeatsmentioning
confidence: 99%
“…As the ARF family traces its origins back to the first land plants, we investigated whether the maize and Arabidopsis ARF binding properties have diverged in the 140-150 million years since their last common ancestor (Finet et al, 2013). Testing a maize co-ortholog of ARF5 (ZmARF29; Galli et al, 2015) on maize gDNA (Zm-gDNA) by DAP-seq, we observed similar, but not identical, motif spacing preferences with two dominant spacing groups in maize compared to the eight more distributed groups in Arabidopsis ( Figure 6C).…”
Section: Cooperative Binding Of Arf Homodimers At Phased Motif Repeatsmentioning
confidence: 99%
“…Furthermore, the Auxin_resp domain is not found in ARFs before plants emerged from an aquatic to land environment. Freshwater algae ancestors of land plants, the charophytes, are reported to contain precursor ARF-like proteins with a B3 domain and domain III/IV, but lack the Auxin_resp domain Finet et al, 2013). The charophyte Klebsormidium flaccidum has an ARF-like protein with an AP2/ERF-related DBD, a B3 domain, and a C-terminal domain III/IV containing the conserved lysine and OPCA motifs found in PB1 domains, but no sequence related to the DD or BRWD found in typical ARF proteins (annotated gene sequence kf100094_0070 in 40528 Klebsormidium flaccidum genome V1.0; Hori et al, 2014).…”
Section: A Second Protein Interaction Module Is Found In Dbd Of Arf Pmentioning
confidence: 99%
“…A lumped internal state, which combines multiple reactions including the binding of auxin to the AFB receptor and related molecular machinery, is represented by x. IAA protein levels are represented by y. The model has eight parameters (k [1][2][3][4][5][6][7][8] ) that intuitively correspond to the biological processes listed in Table 1. We tested the validity of this interpretation numerically by evaluating fits of the data using different assumptions about which parameters change when different ARFs or IAAs are used in the circuit (SI Appendix).…”
Section: Significancementioning
confidence: 99%
“…Limited expression studies available The variable x represents a lumped internal state, which combines multiple reactions including the binding of auxin to the AFB receptor, and the variable y represents IAA protein levels. The model has eight parameters (k [1][2][3][4][5][6][7][8] ) that intuitively correspond to the biological processes listed in Table 1. We focused on three parameters with strong effect on ARC dynamics: IAA expression level (k 3 for IAA and ARF family members indicate that multiple family members are often coexpressed in plant cells, raising the question of how specificity or ordering is encoded (14,15).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation